The Role of Technology in Promoting Collaborative Learning: Case Studies from Multicultural Classrooms - Mansori, Mansori; Hadi, Abdul; Turmudzi, Imam; Jumriah, Jumriah; Anggraheni, Dini (International Journal of Educational Research Excellence (IJERE), 2024)
The objective of this research is to examine the potential of technology in facilitating collaborative learning in a multicultural classroom setting at SMP 11 Jakarta. Given the culturally diverse student backgrounds, this research is concerned with the ways in which technology can facilitate enhanced interaction and collaboration among students from different cultural backgrounds. This research employs a qualitative approach utilising a case study methodology to gain comprehensive insights into the experiences and perceptions of students and teachers regarding the utilisation of technology in collaborative learning. The data were gathered via in-depth interviews, classroom observations, and the examination of pertinent documents. The findings demonstrate that technology not only facilitates communication between students but also fosters a more inclusive and collaborative learning environment. However, there are certain challenges associated with the implementation of technology, particularly with regard to students' digital literacy and the disparity in technology infrastructure across different settings.